Digital literacy and subjective happiness of low-income groups: Evidence from rural China - Wang, Jie; Liu, Chang; Cai, Zhijian (Frontiers in Psychology, 2022)
Improving the happiness of the rural population is an important sign of the effectiveness of relative poverty governance. In the context of the digital economy, discussing the relationship between digital literacy and the subjective happiness of rural low-income groups is of great practicality. Based on the China Family Panel Studies (CFPS) data, the impact of digital literacy on the subjective happiness of rural low-income groups is of great practical significance for relative poverty governance. The findings are as follows: first, we found a significant happiness effect of digital literacy on rural low-income groups. The higher the digital literacy the higher the subjective well-being of the low-income group will be. Second, digital literacy promotes the subjective happiness of rural low-income groups through income increase and consumption growth effects. Third, the happiness effect of digital literacy is heterogeneous among different characteristic groups, and digital literacy significantly impacts the subjective happiness of rural low-income groups. Fourth, decomposing subjective happiness into life satisfaction and job satisfaction, digital literacy significantly positively affects rural low-income groups’ job and life satisfaction. This paper demonstrates that digital literacy has a practical happiness effect. Suppose the government wants to exploit further the subjective welfare effect of digital literacy in the construction of digital villages. In that case, the government should focus on cultivating digital literacy among low-income groups from the demand side and actively promote the construction of digital infrastructure from the supply side.